A Common Fixed Point Theorem in Metric Space under General Contractive Condition - Sunny Chauhan; Zoran Kadelburg; Sumitra Dalal (Journal of Applied Mathematics)
We prove a common fixed point theorem for two pairs of compatible and subsequentially continuous (alternately subcompatible and reciprocally continuous) mappings satisfying a general contractive condition in a metric space. Some illustrative examples are furnished to highlight the realized improvements. Our result improves the main result of Sedghi and Shobe (2007).